Thermodynamic stability of lead-free alkali niobate and tantalate perovskites. Issue 29 (7th August 2015) - Sahu, Sulata K.; Zlotnik, Sebastian; Navrotsky, Alexandra; Vilarinho, Paula M.
<x xml:space="preserve">Abstract</x> Calculated energetics provide key insights into the stability of lead-free alkali niobate and tantalate perovskites.